Sustainable Finance in Islamic Banking: A Systematic Review in the Context of Economic Instability - Anita Kusuma Dewi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Global economic uncertainty in the last ten years due to changes in financial markets, geopolitical conflicts, and the COVID-19 pandemic has tested the resilience of the banking sector, including Islamic banking. This study aims to identify sustainable financial management strategies implemented by Islamic banks using a systematic literature review (SLR) based on the PRISMA approach. A total of 65 relevant scientific articles were analyzed using a thematic approach. The research results revealed three main strategic pillars, namely risk management based on maqashid sharia, ethical and inclusive asset portfolio diversification, and improving financial governance and transparency. Integration of sustainability principles within the sharia framework, including strengthening social fund instruments such as zakat, waqf, and qardhul hasan, as well as value-based digitalization have proven effective in strengthening the resilience and competitiveness of Islamic banks. In addition, adjustments to Environmental, Social, and Governance standards and the establishment of a strategic risk management unit are important elements in maintaining operational continuity amidst global instability. This study contributes theoretical and practical contributions to the development of Islamic finance literature and sustainable development, while also providing policy recommendations to regulators and industry players to realize adaptive and long-term-focused Islamic financial management practices.